Differences In Serum IL-6 Levels Between First-Trimester Normal Pregnancy and Spontaneous Abortion - Vella Amalia; Utama, Bobby Indra; Dessy Arisanty; Nelmi Silvia (Fakultas Kedokteran Universitas Andalas, 2025)
Objectives: In spontaneous abortion cases without previously known predisposing factors, an increase proinflammatory cytokines, especially interleukin 6 (IL-6), found in local and systemic specimens compared to normal 1st -trimester pregnancies. Therefore, IL-6 is thought to have a role in implantation failure in early pregnancy resulting in spontaneous abortion. However, research on serum IL-6 levels in spontaneous abortion patients is still limited in Indonesia. This study aims to determine the difference in serum IL-6 levels in normal pregnancy 1 st - trimester and spontaneous abortion in hospitals in Padang City; Method: This study is an analytical study with a cross-sectional design using secondary data of 21 blood serum samples from each research group at the Biomedical Laboratory of FK Unand. Samples were collected using a consecutive sampling technique. A serum examination was performed with the ELISA technique. Bivariate data analysis using Mann-Whitney statistical test based on data type and distribution; Result: The results showed that the mean value of serum IL-6 levels was 280,56 ng/L in the normal pregnancy group in the 1st -trimester and the median value of the spontaneous abortion group was 279,78 ng/L. There was no significant difference in serum IL-6 levels in normal pregnancy in the 1st -trimester and spontaneous abortion (p = 0,980); Conclusion: This study concluded that there was no difference in serum IL-6 levels between patients with normal pregnancy in the 1st -trimester and spontaneous abortion in hospitals in Padang City. Keywords: Spontaneous abortion, first trimester, serum interleukin 6, cytokines, ELISA